Development of robotic interstitial laser therapy for benign prostatic hyperplasia - Shee, Cheng Yap. (2008)
Interstitial laser coagulation is a relatively new minimally invasive surgical procedure that utilizes laser for performing thermal treatment of non-cancerous prostate enlargement (benign prostatic hyperplasia). The main advantage of interstitial laser coagulation over classical treatment methods (such as open surgery or transurethral resection of the prostate) is safety. When performing this procedure, the laser probe or diffuser tip tends to ricochet off the urethral wall before penetrating into the prostate. Consistent manual penetration including the positioning of the laser probe or diffuser tip is difficult.